Non‐inferiority of microencapsulated mesenchymal stem cells to free cells in cardiac repair after myocardial infarction: A rationale for using paracrine factor(s) instead of cells. Issue 2 (24th April 2019) - Karpov, Andrey A.; Puzanov, Maxim V.; Ivkin, Dmitry Yu.; Krasnova, Marina V.; Anikin, Nikita A.; Docshin, Pavel M.; Moiseeva, Olga M.; Galagudza, Michael M.
Summary: A major translational barrier to the use of stem cell (SC)‐based therapy in patients with myocardial infarction (MI) is the lack of a clear understanding of the mechanism(s) underlying the cardioprotective effect of SCs. Numerous paracrine factors from SCs may account for reduction in infarct size, but myocardial salvage associated with transdifferentiation of SCs into vascular cells as well as cardiomyocyte‐like cells may be involved too. In this study, bone marrow‐derived rat mesenchymal SC (MSCs) were microencapsulated in alginate preventing viable cell release while supporting their secretory phenotype. The hypothesis on the key role of paracrine factors from MSCs in their cardioprotective activity was tested by comparison of the effect of encapsulated vs free MSCs in the rat model of MI. Intramyocardial administration of both free and encapsulated MSCs after MI caused reduction in scar size (12.1 ± 6.83 and 14.7 ± 4.26%, respectively, vs 21.7 ± 6.88% in controls, P = 0.015 and P = 0.03 respectively). Scar size was not different in animals treated with free and encapsulated MSC ( P = 0.637). These data provide evidence that MSC‐derived growth factors and cytokines are crucial for cardioprotection elicited by MSC. Administration of either free or encapsulated MSCs was not arrhythmogenic in non‐infarcted rats. The consistency of our data with the results of other studies on the major role of MSC secretome components in cardiac protection further support the theory that the use of live, though encapsulated, cells for MI therapy may be replaced with heart‐targeted‐sustained delivery of growth factors/cytokines.